Bronsted acidic ionic liquid-catalyzed conversion of hemicellulose into sugars - Matsagar, Babasaheb M.; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2015)
Development of a competent method for the conversion of hemicellulose, a lignocellulosic component, into sugars is essential. In a one-pot method, Bronsted acidic ionic liquid (BAIL)-catalyzed hydrolysis of hardwood hemicellulose at 160 degrees C in water media gave C5 sugars (xylose + arabinose) in 87% yield. The efficiency of the ILs and their acid strength both followed the similar trend, [C3SO3HMIM][HSO4] > [C3SO3HMIM][PTS] > [C3SO3HMIM][Cl] > [BMIM][Cl]. The ion-dipole-type interaction present between the BAIL and the substrate, which is proposed by the H-1 NMR study, is suggested to help in achieving better activity with BAIL than with mineral acid, H2SO4.